Association of Hyperhomocysteinemia with Early Onset Atherosclerotic Peripheral Arterial Occlusive Diseases (Cardiovascular Journal, 2021)
Background: Homocysteine is increasingly recognized as an independent risk factor for vascular disease specially peripheral arterial occlusive diseases. In the present study, an attempt was made to find out the association between the raised fasting plasma total homocysteine level and early onset atherosclerotic peripheral arterial occlusive diseases (PAOD).Methods: In this prospective observational study a total of 50 study subjects were included. All patients were clinically and angiographically documented for atherosclerotic PAOD. All patients underwent surgical intervention as well as estimation of serum total homocysteine level. Arterial segment was sent for histopathological examination to find out whether atherosclerosis was present or not. Patients were divided into two groups- Group-1 included patients of 20-40 years of age and group-II included those of 41-60 years of age. The groups were compared to see association between elevated level of plasma homocysteine and atherosclerotic peripheral arterial occlusive diseases in elderly as well as in early age.Results: 41 (82%) patients were male and 9 (18%) patients were female. Serum homocysteine level was higher in group I than group II (71.4% vs. 40.9%). Besides, the level of mean serum homocysteine level was significantly (p=0.02) higher in group I than group II (21.18±9.53 vs. 17.24±8.92 μmol/L).Conclusion: In conclusion, this study suggests that serum homocysteine has an association with early onset atherosclerotic PAOD. Therefore, a raised serum homocysteine level can be used as an independent biochemical predictor of early onset atherosclerotic PAOD.Cardiovasc. j. 2021; 13(2): 120-127